Economics of Operation of 18 m Fuel Efficient Steel Trawlers of CIFT Design - Gopal, Nikita; G.R., Unnithan; V., Radhakrishnan Nair (Fishery Technology, 2025)
The economic performance of 18 m steel trawler of CIFT design, under commercial operations during 2001-03, is presented. The operation has been profitable even in times of lowering catch and increasing operational expenditure. The operational profit was 47.58 % of the operating costs and the net profit was 7.06% of the total costs indicating the economic viability of the operation. The fuel consumption rate was observed to be 13-14 litres per hour, which establishes the fuel efficiency of the vessel.